The Development of Mind Mapping Learning Model to Increase Group B Students’ Multiple Intelligences at Integrated Paud Al-Furqan in 2019/2020 Academic Year in Kaliwates Jember - Aini Nur Rahmah; Nanik Yuliati; Luh Putu Indah Budyawati (Pancaran Pendidikan, 2019)
Early childhood education is an attempt by educators to provide education from birth to age six years. The highest level of ability children have is intelligence. The intelligence is multiple intelligences. Developing multiple intelligences requires a learning model that is able to develop all intelligences. Based on preliminary observations made at the Al-Furqan Kaliwates Jember Integrated PAUD it was found that the school used a central model. The center model has not been able to develop all the intelligences, becaouse the center uses the center teacher itself is different from the class teacher, so that the intelligence of every child in the center is the  center teacher. So the class teacher does not know firsthand the intelligence that every child has.  This research was conducted to create a new product learning model entitled the development of mind mapping learning models to develop multiple intelligence in the B group of Al-Furqan Kaliwates Integrated PAUD Jember Academic Year 2019/2020. This study aims to find out how the development of learning models and the results of developing mind mapping learning models to develop multiple intelligence. This research uses the R&D method (research and development). Design development uses the ADDIE approach (Analysis, Design, Development, Implementation and Evaluation). Data analysis techniques usiang 1) validation data; 2) practicality data analysis; and 3) effectiveness data abalysis. The results of the development of a mind mapping learning model to develop multiple intelligences is 1) validity aspects usiang validation sheets and RPPH are categorized valid based on the results of the validator’s assessment; 2) aspects of practicality based on learning using the teacher’s ability to manage the mind mapping learning model and observing/evaluating the implementation of the mind mapping learning model fulfilling good and high interpretations, because the instructor’s activities are observes through the observation sheet, and then 3) aspects of the effectiveness of learning usiang the activity instrument children through 3 trials are interpreted to be very high, medium and very high, because bassed on the results of the overall average score of the child’s activity and the teacher’s response to the mind mapping learning model.